Understanding the roles of images and intermodal relationships for optimized use of visual and verbal resources in Vietnam’s textbooks for lower secondary levels - Yusnita Febrianti; Thao Vu (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
The study investigates the roles of images and intermodal relationships of both language and images in two English textbooks used in Vietnamese lower secondary schools, namely Tieng Anh and Solutions textbooks to gain insights on the ways to optimise the use of both language and images as resources in teaching and learning activities. Kress and Van Leeuwen’s (1996, 2006) framework on the grammar of visual design is used to analyse the images, looking at the types of image representations and the compositional meanings. The language-image relationships in the books, on the other hand, are analysed using the framework of Intermodal Identification (Unsworth & Cleirigh, 2014). Intermodal identification is built on the notion that language complements the meaning of the image and vice versa. Language identifies image by glossing the image participants which are not encoded in the language elements. Image identifies language in three aspects: intensive to visualise quality such as shape, colour, or texture, possessive to visualise additional participants which are not explicitly addressed in the language and circumstantial to visualise the elements of locations in the language.  While image in textbooks has always been considered essential as a source of teaching and learning materials as well as helping students to learn, this study suggests that the role of image is augmented when juxtaposed with the accompanying language. The study implies the need for further investigation, for example in the classroom action research on how language and image resources can be utilised in teaching and learning activities.  Also, the result of the study may be replicated to analyse language-image relationship in different samples of textbooks.Keywords: images, language,English textbooks, language-image relationship/interactionMemahami peran gambar dan hubungan intermodal untuk optimalisasi penggunaan sumber visual dan verbal dalam buku teks bahasa Inggris untuk siswa sekolah menengah di VietnamPenelitian ini menyelidiki peran gambar dan hubungan antar moda dari kedua bahasa dan gambar dalam dua buku teks bahasa Inggris yang digunakan di sekolah menengah pertama Vietnam, yaitu buku teks Tieng Anh dan Solutions untuk mendapatkan wawasan tentang cara mengoptimalkan penggunaan bahasa dan gambar sebagai sumber daya di kegiatan belajar mengajar. Kerangka kerja dari Kress dan Van Leeuwen (1996, 2006) tentang tata bahasa desain visual digunakan untuk menganalisis gambar, melihat jenis representasi gambar dan makna komposisi. Kemudian, hubungan bahasa-gambar dalam buku dianalisis menggunakan kerangka Identifikasi Intermodal (Unsworth & Cleirigh, 2014). Identifikasi intermodal dibangun di atas gagasan bahwa bahasa melengkapi makna gambar dan sebaliknya. Bahasa mengidentifikasi gambar dengan mengilapkan peserta gambar yang tidak dikodekan dalam elemen bahasa. Gambar mengidentifikasi bahasa dalam tiga aspek: intensif untuk memvisualisasikan kualitas seperti bentuk, warna, atau tekstur, posesif untuk memvisualisasikan peserta tambahan yang tidak secara eksplisit dibahas dalam bahasa dan sirkumstansial untuk memvisualisasikan elemen lokasi dalam bahasa. Sementara gambar dalam buku teks selalu dianggap penting sebagai sumber bahan ajar dan pembelajaran serta membantu siswa untuk belajar, penelitian ini menunjukkan bahwa peran gambar bertambah ketika disandingkan dengan bahasa yang menyertainya. Penelitian ini menunjukkan pentingnya penelitian lanjutan, misalnya dalam bentuk penelitian tindakan kelas untuk mengetahui bagaimana bahasa dan gambar dapat dimanfaatkan dalam kegiatan belajar mengajar. Juga, hasil penelitian ini dapat direplika untuk menganalisis hubungan bahasa-gambar dalam sampel buku teks yang berbeda.Kata kunci: bahasa, gambar, buku teks, bahasa Inggris, hubungan/interaksi bahasa-gambar